RECICLAGEM DE BATERIAS DE ÍONS DE LÍTIO DE APARELHOS CELULARES: RECUPERAÇÃO DO SOLVENTE ORGÂNICO DO ELETRÓLITO ATRAVÉS DA ADSORÇÃO EM CARVÃO ATIVADO - Peres, Bruno; Bertuol, Daniel Assumpção (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704251 The recycling of electronic equipment has become essential due to the scarcity of naturalresources associated with the increasing development of new technologies for these deviceswhich become obsolete in an increasingly faster. Most mobile phones are manufactured equippedwith lithium-ion batteries. These batteries are composed of a cathode, an anode and a separatorbetween them that is embedded in an organic solvent with lithium salts, which acts as anelectrolyte. The organic solvent comprises a mixture of carbonates. Studies on the recycling of LiIonbatteries generally aim to recover the metals present in their composition, such as copper. Butso far there is little information available about the recovery of organic solvent present in the LiIonbatteries. That this solvent is toxic and polluting. The objective of this study was to quantifythe solvent and prevent the emission of solvent from the activated carbon adsorption. As a result,we obtained a considerable amount of volatiles in the batteries, 9 to 12% of the total weight ofthese. The adsorption of solvent was made in an equipment with activated carbon. Adsorbed on The recycling of electronic equipment has become essential due to the scarcity of naturalresources associated with the increasing development of new technologies for these deviceswhich become obsolete in an increasingly faster. Most mobile phones are manufactured equippedwith lithium-ion batteries. These batteries are composed of a cathode, an anode and a separatorbetween them that is embedded in an organic solvent with lithium salts, which acts as anelectrolyte. The organic solvent comprises a mixture of carbonates. Studies on the recycling of LiIonbatteries generally aim to recover the metals present in their composition, such as copper. Butso far there is little information available about the recovery of organic solvent present in the LiIonbatteries. That this solvent is toxic and polluting. The objective of this study was to quantifythe solvent and prevent the emission of solvent from the activated carbon adsorption. As a result,we obtained a considerable amount of volatiles in the batteries, 9 to 12% of the total weight ofthese. The adsorption of solvent was made in an equipment with activated carbon. Adsorbed onactivated carbon were approximately 27.38% of the solvent from the battery. This process seemedto be effective to a point where one can no longer adsorb the solvent for possibly carbon reachedits maximum adsorption capacity. Another reason for the low yield of the adsorption may be dueto reactions of the solvent with water in the air in the moment of the opening of the battery.